Strategi Guru Mata Pelajaran Akidah Akhlak dalam Meningkatkan Kedisiplinan Belajar Siswa - Nurjannah, Eka; Masudi, Masudi; Baryanto, Baryanto; Deriwanto, Deriwanto; Karolina, Asri (JOEAI (Journal of Education and Instruction), 2020)
This study aims to find out how the teacher strategies of the subjects Akidah Akhlak in improving student learning discipline and how the state of student learning discipline in SDIT Rabbi Radhiyyah 01 rejang lebong district. This research uses qualitative approach with field research type. Observation data collection techniques, interviews, and documentation. Data analysis includes data reduction, data presentation, verification/drawing conclusions. The results showed; First, the teacher's strategy of morality in improving student learning discipline by briefing students on the importance of enforcing discipline, teachers setting an example for students in good manners, teachers advising students to be good and teachers to sanction students who violate discipline; Second, the student's learning discipline situation is informed if the student's low interest in learning is due to students lacking introspection, weak student punishment and low support from some parents. In conclusion, the strategies implemented by teachers in improving student discipline by providing examples, advice to be good, as well as weak student discipline conditions caused by students lacking self-introspection, weak student punishment and low support of some parents. Keywords: Teacher Strategy, Moral Code Teachers, Learning Discipline